Rapid Microwave Digestion Procedures for the Elemental Analysis of Alloy and Slag Samples of Smelted Ocean Bed Polymetallic Nodules - Kumari Smita; Saurabh Kumar Singh; Brajesh Kumar (Journal of Chemistry)
The use of microwave digester for digestion of alloy and slag samples of smelted ocean bed polymetallic nodules has permitted the complete digestion of samples, thereby replacing the tedious classical methods of digestion of samples. The digestion procedure includes two acid-closed digestions of samples in a microwave oven. Owing to the hazardous nature of perchloric acid, it was not used in developed digestion procedure. Digested sample solutions were analyzed for concentrations of various radicals and the effectiveness of the developed digestion methodology was tested using certified reference materials. It was found that the developed method is giving results comparable with that obtained from conventionally digested samples. In this digestion procedure, time required for digestion of samples was reduced to about 1 hour only from 8-9 hours of conventional digestion.